Delayed Acute Ischemia as a Consequence of Multi-Ligament Injury of the Left Knee Following a Motorcycle Accident - Laura Leci Tahiri; Lisa Tahiri (Journal of Endovascular Resuscitation and Trauma Management)
Motorcycle accidents can cause complex orthopedic and vascular injuries, posing diagnostic and treatment challenges. We present a case of a 34-year-old Albanian man with a multi-ligament knee injury and arterial thrombosis in his left leg following a motorcycle accident. The patient initially received conservative care but developed severe leg pain, coldness, and numbness, prompting urgent vascular imaging. Imaging confirmed popliteal artery thrombosis, necessitating surgical intervention. This case highlights the severe complications of motorcycle accidents, emphasizing the need for prompt vascular injury detection and a multidisciplinary approach in trauma management. Early recognition and timely intervention are crucial to prevent long-term morbidity and to optimize recovery. Further research is needed to improve diagnostic and treatment strategies for vascular complications in such injuries.